Cardiac Orienting Responses Differentiate the Impact of Prenatal Alcohol Exposure in Ukrainian Toddlers. (21st September 2016) - Kable, Julie A.; Coles, Claire D.; Jones, Kenneth L.; Yevtushok, Lyubov; Kulikovsky, Yaroslav; Wertelecki, Wladimir; Chambers, Christina D.; ,
Abstract : Background: Prenatal alcohol exposure (PAE) has been found to impact neurophysiological encoding of environmental events negatively in the first year of life but has not been evaluated in older infants or toddlers. Cardiac orienting responses (ORs) collected during a habituation/dishabituation learning paradigm were obtained from 12‐ to 18‐month‐olds to assess the impact of PAE beyond the first year of life. Methods: Participants included women and their toddlers who differed in PAE histories and enrolled in a randomized clinical trial of multivitamin/mineral usage during pregnancy. Those who were randomly assigned to the no intervention group were used for this analysis. The habituation/dishabituation paradigm consisted of 10 habituation and 5 dishabituation trials. Baseline heart rate (HR) was collected for 30 seconds prior to stimulus onset, and responses to the stimuli were assessed by sampling HR for 12 seconds poststimulus onset. Results: The speed of the OR in response to auditory stimuli in the dishabituation condition was found to be altered as a function of maternal alcohol use around conception. For visual stimuli, positive histories of PAE were predictive of the magnitude but not the speed of the response on habituation and dishabituation trials. A history of binge drinking was associated with reduced magnitude of the OR response on visual encoding trials, and level of alcohol exposure at the time of conception was predictive of the magnitude of the response on visual dishabituation trials. Conclusions: Cardiac ORs collected in the toddler period were sensitive to the effects of PAE. The magnitude of the OR was more sensitive to the impact of PAE than in previous research with younger infants, and this may be a function of brain maturation. Additional research assessing the predictive utility of using ORs in making decisions about individual risk was recommended. Abstract : Prenatal alcohol exposure (PAE) has been found to impact neurophysiological encoding of environmental events in the first year of life but has not been evaluated beyond the first year of life. Toddler's cardiac orienting responses (OR) collected during a habituation/dishabituation learning paradigm were sensitive to the effects of PAE. The magnitude of the OR was more sensitive to the impact of PAE than in previous research with younger infants, and this may be a function of brain maturation.